2020
DOI: 10.2337/figshare.13348094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficiency of Stat1 in CD11c+ Cells Alters Adipose Tissue Inflammation and Improves Metabolic Dysfunctions in Mice Fed High-Fat Diet

Abstract: <a>CD11c<sup>+</sup> macrophages/dendritic cells (MDCs) are increased and display classically activated M1-like phenotype in obese adipose tissue (AT) and may contribute to AT inflammation and insulin resistance. Stat1 is a key transcription factor for MDC polarization into M1-like phenotype. Here, we examined the role of Stat1 in obesity-induced AT MDC polarization and inflammation and insulin resistance using mice with specific knockout of Stat1 in MDCs (cKO). Stat1 was upregulated and phos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…CD11c + myeloid cells are active members in obese adipose tissue [16,17,34]. To investigate the role of Lkb1 in adipose tissue CD11c + cells, we thus generated Lkb1 conditional knockout CD11c Cre Lkb1 f/f mice and established a diet-induced obesity (DIO) model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD11c + myeloid cells are active members in obese adipose tissue [16,17,34]. To investigate the role of Lkb1 in adipose tissue CD11c + cells, we thus generated Lkb1 conditional knockout CD11c Cre Lkb1 f/f mice and established a diet-induced obesity (DIO) model.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidences have elaborated adipose immune status is closely associated with obesity and threatening metabolism disorders [1,8,35]. CD11c + myeloid cells are involved in overnutrition associated immune-metabolic disorders [14,16,17,36], therefore, understanding of the underlying molecular basis becomes essential in developing intervention strategies for these threatens. Previous studies have revealed the critical role of the nutrient sensor Lkb1 in controlling the function of splenic and lymphoid CD11c + dendritic cells [28,29,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation